Evaluasi Pengelolaan Limbah B3 di Rumah Sakit Sebelum dan Setelah Covid-19 (Studi Kasus Rumah Sakit Umum Daerah Dr. Moewardi Solo) - Nugraha, Ferry Satya Adi; Raharjo, Mursid; Budiyono, Budiyono (Jurnal Riset Kesehatan Masyarakat, 2022)
Dr. Moewardi Regional General Hospital is one of the hospitals appointed by the Surakarta local government to provide services and handling related to the COVID-19 pandemic. Providing health services in hospitals has made the hospital one of the largest producers of waste with various types. Especially with the current COVID-19 pandemic conditions, causing the amount of medical waste to increase. This study aims to evaluate the management of hospital B3 solid waste from the reduction and sorting stage, the storage stage, and carriage stage under Regulation Ministry of Environment and Forestry No. 56 in 2015 on Procedures and Technical Requirements to Manage Hazardous and Toxic in Health Care Facilities. The type of research is descriptive method with qualitative approach with primary and secondary data—the data obtained by in-depth interviews of the selected informants, moreover, for complementing data observation. The result of this research had the amount of waste before the pandemic had an average per day was 663,086 Kg, and after the pandemic, the average waste per day was 736.45 Kg, it can seem that there was an 11.1% increase in the amount of garbage. The evaluation based on the regulation of the Minister of Environment and Forestry Number 56year 2015 gets a percentage of 90.57%, which means do not meet the standard of 100%. The finding of management, such as self-considering from putting the waste that fit with the labels, and the negligence officer in usage self-protection tools in the incinerator storage and carriage stage.